Regional Financial Integration in the Caribbean : Evidence From Financial and Macroeconomic Data - Kwon, Goohoon (IMF Working Papers; Working Paper, 2009)
This paper assesses the extent of regional financial integration in the Caribbean Community (CARICOM) by analyzing equity prices in the region and rigidity of external financing constraints. The results are presented in a cross-regional perspective. The Caribbean stock markets are not as well integrated as one would expect from the extent of cross-listing and importance of regional banking groups: price differentials of cross-listed stocks reach an average of 5 percent. Auto-Regressive models suggest that these price differentials are only slowly arbitraged away, with half-lives exceeding 7 worked days, even when looking only at large arbitrage opportunities (using a Threshold Auto-Regressive model). A speculative methodology using macroeconomic data seems to confirm these findings. A strong mean reversion of the current account (respectively regional trade imbalances) is interpreted, following Obstfeld and Taylor (2004), as a lack of ways to finance current account deficits, id est a lack of global (respectively regional) financial integration. The region appears to be much less integrated than the EU15 or the ASEAN+3 groups, although it fares well compared to other LDCs.